(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2020)
ABSTRACT Â Cane is one of the plantation commodities managed as raw material for making sugar. PT. Cinta Manis as one of the sugar producers has sugarcane production and management activities on a large scale. Production of sugar with raw material in large quantities every day, produces a by-product of sugarcane bagasse waste. Currently sugarcane bagasse waste is only used as compost after going through several stages of processing. The study was conducted in a laboratory by physically changing cane bagasse to ash through burning. Furthermore, the ash from the sugarcane bagasse was added to high quality concrete K-300. The results of the laboratory tests carried out showed that the addition of Cane Bagasse Ash (CBA) by 5% can increase the compressive strength of the concrete 6.43% higher than the normal compressive strength of the concrete. However, the addition of CBA which is greater than 5% to the cement in the concrete actually decreases the quality of the compressive strength of the concrete. This means that the 5% CBA content can be used to increase the compressive strength of concrete.